Reinterpretation of “Fitna” in QS. al-Baqarah: 191 (Ma’na Cum Maghzā Approach) - Fajar Wati, Erika Aulia; Hakam al-Ma’mun (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The meaning of the word “fitna” in Indonesian is often incorrect when it is associated with the word of Allah written in QS. al-Baqarah: 191. The snippet of the verse is al-fitna asyaddu min al-qatl, which if translated reads more or less